Beyond the Numerator: Visualizing the Equal Partitioning Barrier in Elementary Fraction Learning - Davina Aurelia; Slamet Arifin; Siti Faizah (Universitas Negeri Malang, 2026)
Abstract: Understanding fractions remains a persistent challenge for elementary students, particularly when translating verbal mathematical problems into visual representations. This study aims to analyze the visual-conceptual difficulties of elementary school students in understanding fractions, specifically the principles of equal partitions and equivalence fraction, through visual representations. Using a thematic content analysis within a descriptive qualitative design, six fifth-grade students were selected based on their mathematical representation skills. Instruments included an illustrated diagnostic test (6 figures) and semi-structured interviews. The results reveal that the majority of students exhibited significant misconceptions rooted not in an inability to see differences, but in a